Immunogenicity and safety of an Escherichia coli-produced 9-valent human papillomavirus vaccine (types 6/11/16/18/31/33/45/52/58) in healthy Chinese women aged 20–45 years: a single-center, randomized, observer-blinded, positive controlled phase 2 clinical trial - Wei, Mingwei; Liu, Hongyan; Yu, Hongyang; Pan, Hongxing; Tao, Hong; Zhang, Jing; Han, Weiwei; Wu, Dan; Wang, Wenjuan; Li, Jingxin (Frontiers in Immunology, 2025)
BackgroundVaccination with prophylactic human papillomavirus (HPV) vaccines is one of the most effective measures to prevent cervical cancer and other related diseases. Here we aimed to evaluate the immunogenicity and safety of an Escherichia coli-produced 9-valent human papillomavirus (9vHPV) vaccine.MethodWe did a single-center, randomized, observer-blinded, positive controlled phase 2 clinical trial in healthy women aged 20–45 years. All eligible participants were randomly assigned (1:1:1) to receive 270 ug 9vHPV, 360 ug 9vHPV, or the control vaccine (Gardasil) with a 0–2–6-month schedule. Serum samples were collected at day 0 and month 7 to assess IgG and neutralizing antibodies (nAbs). For HPV 6/HPV 11/HPV 16/HPV 18, non-inferiority was identified for the lower limit of the 95% CI of the geometric mean titer (GMT) ratio at a margin of 0.5 and a seroconversion rate (SCR) difference at a margin of -5%. For HPV 31/HPV 33/HPV 45/HPV 52/HPV 58, superiority was demonstrated if the lower limit of the 95% CI for GMT ratio is greater than 1.ResultsA total of 780 participants aged 20–45 years were enrolled, among whom 770 completed the three-dose immunization schedule. The incidences of ARs within 7 days in the 270 μg, 360 μg, and positive control groups were 38.85%, 41.92%, and 22.69%, respectively (P < 0.001). The GMTs of nAbs and IgG antibodies for nine HPV types in both 270 ug and 360 ug groups showed an obvious rise at month 7. For HPV 31/HPV 33/HPV 45/HPV 52/HPV 58, the GMTs of nAbs in both 270 μg and 360 μg groups were higher than those in the positive control group, with the 95% CI lower bounds of GMT ratios all greater than 1. Compared to the positive control group, HPV 6 and HPV 18 achieved non-inferiority criteria for GMT in both dose groups. However, the GMT ratio of HPV 16 in the 270 μg group was 0.46 (0.38–0.55), and HPV 16 and HPV 11 in the 360 μg group were 0.48 (0.40–0.58) and 0.53 (0.46–0.60), respectively. The SCRs of nAbs for HPV 6/HPV 11/HPV 16/HPV 18 in the three groups were 100%, with the 95% CI lower bound for SCR differences ranging from -2.55% to -1.64%.ConclusionThe candidate 9vHPV vaccine was well tolerated and immunogenic, supporting further evaluation for efficacy and safety in larger populations.Clinical Trial Registrationhttps://clinicaltrials.gov, identifier NCT05694728.